Tertiary Education at a Glance: China - Yu, Kai.; Stith, Andrea Lynn.; Liu, Li.; Chen, Huizhong; SpringerLink (Online service) (Rotterdam : SensePublishers, 2012)
This publication aims to provide a comprehensive and up-to-date overview of tertiary education in China. It is the result of a partnership established between the World Bank and the Shanghai Jiao Tong University$1 (Bs Graduate School of Education to collect and disseminate information on higher education in the China. Inspired by the OECD$1 (Bs annual (3z(BEducation at a Glance(3y (Bpublication, it presents data collected from several sources, including statistical publications such as the National Statistics on Education Yearbook and other statistical yearbooks, government authorities such as the Chinese Ministry of Education, and other sources, and is a significant and timely contribution to the literature and data on global tertiary education. As such, it should constitute a valuable resource for students, scholars, and policy makers interested in understanding tertiary education in the world$1 (Bs most populous country.s
Keywords: Education; Education, Higher; Education; Higher Education